Evaluation of 12 Multi-InDel markers for forensic ancestry prediction in Asian populations. (November 2019) - Sun, Kuan; Yun, Libing; Zhang, Chen; Shao, Chengchen; Gao, Tianzhen; Zhao, Ziqin; Hou, Yiping; Xie, Jianhui; Tang, Qiqun
Highlights: Multi-InDels were employed to investigate Asian population stratification. Sub-structures in Asia were detected through genotypes of the 12 Multi-InDels. Serial dimensionality reduction was first applied in forensic genetic analysis. Basic data of Multi-InDels for three Asian populations was gathered. Abstract: Various types of genetic markers have been applied to forensic ancestry inference. Biallelic markers, such as SNPs and InDels, have proven to be optimal choices except for the low information content provided by a single locus. Multi-InDel marker is defined as a specific DNA fragment with several InDel markers located tightly in the physical position. Previous research indicates that multi-InDel markers perform well in population analysis and ancestry inference because of higher degree of polymorphism and remarkable population differences. In this study, a panel consisting of 12 multi-InDel markers was employed to evaluate the general performance in forensic practice and the discrimination power for population analysis. Sample types encountered in routine forensic practice were genotyped to validate the feasibility of regular use. A population study was performed on a total of five Asian populations to verify the discrimination power. Moreover, a double-blind test for ancestry prediction was conducted to assess the predictive capability. In conclusion, these results revealed the significance of multi-InDel markers for population structure stratification. The present panel showed the potential as a valid complementary tool in forensic applications.